HIERARCHICAL CLUSTERING ANALYSIS OF SUSTAINABLE SOCIETY INDICATORS (Third Sector Social Economic Review, 2019)
First of all, the concept of sustainability, which is aimed at protecting natural resources, preventing climate change and protecting ecological systems, has started to be examined from a wide perspective with the inclusion of social and economic dimensions. The sustainable society index consisting of human welfare, environmental welfare, and economic welfare dimensions has been formed in order to measure sustainability effectively. The present study aims to classify 154 countries in human welfare, environmental welfare and economic welfare using basic needs, personal development-health, well-balanced society, natural resources, climate-energy, transition and economy sub-dimensions by applying hierarchical clustering analysis. Hierarchical clustering analysis results show that countries’ cluster memberships differ from each other in terms of human welfare, environmental welfare, and economic welfare. In addition, when the sustainable society index rankings of the countries are examined, it is observed that in the human welfare dimension, Finland, Germany, Netherlands, Iceland and Norway; in the environmental welfare dimension, Burundi, Togo, Lesotho, Central African Republic and Uganda; in the economic welfare dimension, countries such as Norway, Switzerland, Estonia, Sweden and Czechia are in the first place. Consistent with the results of clustering analysis, it is revealed that the top-ranked countries are in highly developed countries in terms of human, environmental and economic welfare.
Keywords: Sustainable Society Index; Human Welfare; Environmental Welfare; Economic Welfare; Hierarchical Cluster Analysis